Species identity crisis among New World members of the genus Heliothrips (Thysanoptera: Thripidae: Panchaetothripinae) - Silva, Larinne De Maria Rocha; O’donnell, Cheryle A.; Lima, Élison Fabrício Bezerra (Zootaxa, 2024)
Until mid-1990s, Heliothrips was considered a genus without major identification problems, with only H. haemorrhoidalis spread worldwide. More recently, concerns have arisen regarding misidentifications of this pest species around the world, particularly with the description of H. longisensibilis from China and the subsequent records from Argentina and Brazil. Here we consider that species as a new synonym of H. angustior stat. rev., and records of this species under the name H. haemorrhoidalis from the Neotropics (and also India and Thailand) are rectified, whereas in the Nearctic region only H. haemorrhoidalis is present. Both species are widespread, and morphological variations suggest other cryptic species may occur. Heliothrips flamengo sp. n. is described from the Brazilian and Peruvian Amazon Rainforest, and an updated key to the five species of Heliothrips is provided.